Optimal 18F-fluorination conditions for the high radiochemical yield of [18F]AlF-NOTA-NHS complexes - Hassan, Hishar; Othman, Muhammad Faiz; Abdul Razak, Hairil Rashmizal (De Gruyter, 2021)
18F-fluorination using aluminum-fluoride ([18F]AlF) chelate technique has been reported to give a low-to-moderate radiochemical yield, between 5 and 20%. Therefore, the work described here outlines the optimum 18F-fluorination condition for the formation of [18F]AlF2+ and [18F]AlF-NOTA-NHS complex with the radiochemical yield (RCY) and purity (RCP) of more than 90% as a prerequisite step before proceeding with the radiopharmaceutical preparation using the [18F]AlF-bifunctional chelator technique. As well as being simple, the suggested method is practical and relevant for beginners interested in 18F-fluorination with [18F]AlF-chelate complex technique or also for a researcher who aims to proceed on an extensive scale.